2001
DOI: 10.1101/gad.859201
|View full text |Cite
|
Sign up to set email alerts
|

Putative telomere-independent mechanisms of replicative aging reflect inadequate growth conditions

Abstract: Telomere shortening is the mechanism underlying replicative aging in fibroblasts. A variety of reports now claim that inactivation of the p16 INK4a/pRB pathway is required in addition to telomere maintenance for the immortalization of cells such as skin keratinocytes and breast epithelial cells. We here show that the premature growth arrest of these cell types can be explained by an inadequate culture environment. Providing mesenchymal/epithelial interactions by cultivating the telomerase-expressing cells on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
370
5
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(390 citation statements)
references
References 39 publications
13
370
5
2
Order By: Relevance
“…The intrinsic, telomere-dependent senescence is triggered by accumulation of shortened and dysfunctional telomeres with altered telomeric state (Harley et al, 1990;Karlseder et al, 2002). The extrinsic senescence is telomere-independent and triggered in cells after exposure to environmental factors, such as genotoxic stress, in vitro culture shock, and oncogenic stimuli (Serrano et al, 1997;Ramirez et al, 2001;Itahana et al, 2004;Chen et al, 2005;Dimri, 2005). The onset of extrinsic senescence is frequently associated with induction of p16 INK4A (Itahana et al, 2004).…”
mentioning
confidence: 99%
“…The intrinsic, telomere-dependent senescence is triggered by accumulation of shortened and dysfunctional telomeres with altered telomeric state (Harley et al, 1990;Karlseder et al, 2002). The extrinsic senescence is telomere-independent and triggered in cells after exposure to environmental factors, such as genotoxic stress, in vitro culture shock, and oncogenic stimuli (Serrano et al, 1997;Ramirez et al, 2001;Itahana et al, 2004;Chen et al, 2005;Dimri, 2005). The onset of extrinsic senescence is frequently associated with induction of p16 INK4A (Itahana et al, 2004).…”
mentioning
confidence: 99%
“…When grown in co-culture with post-mitotic fibroblast feeder cells, human keratinocytes, exhibit a delay in passage dependent p16 INK4a (p16) expression and have an extended lifespan in culture (Ramirez et al, 2001;Rheinwald et al, 2002;Baek et al, 2003;Fu et al, 2003;Kang et al, 2003;Darbro et al, 2005). We have found that co-culture of keratinocytes with feeder cells delays the accumulation of p16 protein but does not prevent the eventual increase of p16 expression in late passage keratinocytes cultured with feeder cells .…”
Section: Introductionmentioning
confidence: 77%
“…Previous reports have suggested that human keratinocytes can be immortalized by telomerase activity alone when grown in co-culture with fibroblast feeder cells (Ramirez et al, 2001;Harada et al, 2003). Furthermore, these studies suggest that p16 expression in TERTimmortalized keratinocytes is not inactivated and remains inducible by either transfer to plastic culture conditions or exposure to UV irradiation.…”
Section: Tert Immortalization Of Co-cultured Human Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, constitutive ectopic hTERT expression is insufficient to immortalize other cell types including keratinocytes, human mammary epithelial cells (HMECs), (Kiyono et al 1998), airway epithelial cells (Lundberg et al 2002), and preadipocytes (Darimont et al 2003) although in some cases, culture conditions permit cell immortalization with the expression of hTERT (Ramirez et al 2001). Immortal keratinocyte clones that eventually arise after the overexpression of hTERT show evidence of inactivation of the retinoblastoma (RB)/p16 INK4A tumor-suppressor pathway (Kiyono et al 1998;Dickson et al 2000).…”
Section: Barriers To Immortalization: Replicative Senescencementioning
confidence: 99%